Excessive daytime napping independently associated with decreased insulin sensitivity in cross-sectional study – Hyogo Sleep Cardio-Autonomic Atherosclerosis cohort study - Kakutani-Hatayama, Miki; Kadoya, Manabu; Morimoto, Akiko; Miyoshi, Akio; Kosaka-Hamamoto, Kae; Kanzaki, Akinori; Konishi, Kosuke; Kusunoki, Yoshiki; Syoji, Takuhito; Koyama, Hidenori (Frontiers in Endocrinology, 2023)
Background: Although excessive daytime napping has been shown to be involved in diabetes occurrence, its impact on insulin secretion and sensitivity has not been elucidated. It is speculated that excessive napping disrupts the sleep-wake rhythm and increases sympathetic nerve activity during the day, resulting in decreased insulin sensitivity, which may be a mechanism leading to development of diabetes. We previously conducted a cross-sectional study that showed an association of autonomic dysfunction with decreased insulin sensitivity, though involvement of autonomic function in the association between napping and insulin sensitivity remained unclear. Furthermore, the effects of napping used to supplement to short nighttime sleep on insulin secretion and sensitivity are also unknown. In the present cross-sectional study, we examined the relationships of daytime nap duration and autonomic function with insulin secretion and sensitivity in 436 subjects enrolled in the Hyogo Sleep Cardio-Autonomic Atherosclerosis (HSCAA) Cohort Study who underwent a 75-g oral glucose tolerance test (75-g OGTT), after excluding those already diagnosed with diabetes. Methods: Daytime nap duration was objectively measured using actigraphy, with the subjects divided into the short (≤1 hour) and long (>1 hour) nap groups.Insulin secretion and sensitivity were determined using 75-g OGTT findings.Standard deviation of normal to normal R-R interval (SDNN), a measure of autonomic function, was also determined based on heart rate variability.Subgroup analysis was performed for the associations of napping with insulin secretion and sensitivity, with the results stratified by nighttime sleep duration of less or greater than six hours.Results: Subjects in the long nap group exhibited lower insulin sensitivity parameters (QUICKI: β=-0.135, p<0.01; Matsuda index: β=-0.119, p<0.05) independent of other clinical factors. In contrast, no associations with insulin secretion were found in either group. Furthermore, the association of long nap duration with insulin sensitivity was not confounded by SDNN. Specific subgroup analyses revealed more prominent associations of long nap habit with lower insulin sensitivity in subjects with a short nighttime sleep time (β=-0.137, p<0.05).Long daytime nap duration may be a potential risk factor for decreased insulin sensitivity.